2018
DOI: 10.4103/ijpvm.ijpvm_367_17
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of zinc supplementation as adjuvant therapy for dengue viral infection in Thai children

Abstract: Background:Zinc deficiency is common in developing countries and increases the risk for several infectious diseases. Low serum zinc levels have been reported in children with dengue virus infection (DVI). This study aimed to assess the effects of zinc supplementation on DVI outcomes.Methods:A double-blinded, randomized trial was conducted in 50 children with dengue fever (DF)/dengue hemorrhagic fever admitted to the pediatric unit of MSMC Srinakharinwirot University Hospital, Thailand, between January 2016 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Zinc. Rerksuppaphol and Rerksuppaphol 25 conducted an RCT in 50 children (mean age 6.3 years) with DF at an academic medical center in Bangkok, Thailand. Patients were randomized to receive either: 1) 15 mg oral bis-glycinate zinc three times daily for 5 days or until defervescence, or 2) placebo.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Zinc. Rerksuppaphol and Rerksuppaphol 25 conducted an RCT in 50 children (mean age 6.3 years) with DF at an academic medical center in Bangkok, Thailand. Patients were randomized to receive either: 1) 15 mg oral bis-glycinate zinc three times daily for 5 days or until defervescence, or 2) placebo.…”
Section: Resultsmentioning
confidence: 99%
“…14 Zinc supplementation was associated with shorter duration of hospitalization. 25 There is limited previous research investigating relationships between micronutrient supplementation and clinical outcomes in DF patients. A 2014 review by Ahmed et al 15 summarized existing work on micronutrients and dengue, but at the time of its publication, there were only two articles evaluating the use of micronutrient supplements in the clinical treatment of DF patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…66 A study of zinc supplementation as an adjunctive treatment for DENV infection in Thai children revealed that 46% of children admitted with DF/DHF had a zinc deficiency. 67 These children had a longer hospitalization than those with regular zinc levels, regardless of zinc supplementation. Although the time to defervescence does not benefit from zinc supplementation, children with basal normal zinc levels and with zinc supplementation demonstrated a shorter duration of fever.…”
Section: Zinc Supplementationmentioning
confidence: 92%